Traditional communities, traditional landscapes? Afro- descendant landscapes in the Colombian Pacific region - Aguirre, C. Nancy (JOURNAL OF LANDSCAPE ECOLOGY, 2019)
This work addresses gender dimensions of traditional agricultural landscapes, in collective lands titled to Afro-descendant communities in the Pacific region of Colombia, South America. Historical and current information on environmental, socio-economic and settlement processes provided a comprehensive portrait at a subdivision of the collective land-title “Los Delfines”, named “El Cedro”. The remote sensing process (a mainstream method for identifying land use and land cover change) helped exploring the spatial setting of this traditional landscape under the lenses of researching their gendered dimensions. Statistical analyses on both census data (secondary data) and survey sample data (fieldwork data) allowed to reassert a set of three groups of gendered land uses, namely, women-akin, men-akin, and gender-inclusive uses. However, a narrative perspective helped to bond previous theoretical, spatial and quantitative outcomes, under the lenses of the practical experience of fieldwork, which also by way of participatory observation and semi-unstructured interviews brought to the researcher (me) valuable insights and information besides the previous outcomes. The found rearrangement of settlement spaces and production systems provided practical indications that women´s roles, decisions, and strategies on this traditional landscape have restructured settlement patterns, and landscape dynamics of large areas at heterogeneous spatial and temporal scales.